In-depth Analysis of Students' Mathematical Problem-Solving Skills: Influence Factors Motivation and Effective Teaching Strategies - Tririnika, Yuliana; Suryadi, Imam; Slamet, Isnandar (AL-ISHLAH: Jurnal Pendidikan, 2024)
Problem-solving (PS) skills are efforts to find solutions when faced with challenges. This study aims to examine students' mathematical PS skills by focusing on the influence of learning motivation and identifying factors that were previously overlooked. A qualitative approach with a case study design was used, where the researcher acted as the primary instrument. The research also utilized PISA-type test instruments, observation sheets, and interviews. PISA-type questions were designed around content, context, and process components, adhering to the PISA framework. The study was conducted in a school in Surakarta, chosen for its alignment with the minimum competency assessment system similar to PISA. Using snowball sampling, nine students were selected for response analysis. These students were categorized based on their motivation levels: high, moderate, and low. The results show that students with high motivation are proactive in problem-solving, directly addressing the problem, reviewing each step as they proceed, and ensuring accuracy. Moderately motivated students take more time, often using scratch paper, and review their work only at the end. Low-motivation students face greater difficulties, frequently making mistakes, relying heavily on scratch paper, and often skipping the review process due to time pressure. To improve PS skills, future research could explore the integration of interactive digital tools with instant feedback, adaptive learning platforms tailored to student motivation, and collaborative learning exercises. Additionally, incorporating real-world scenarios into problem-based learning could enhance engagement and develop deeper problem-solving abilities across different motivation levels.